Delayed prediction of idiom constituent meaning points to weak holistic multi-word representation in children. Issue 8 (14th September 2022) - Kessler, Ruth; Friedrich, Claudia K.
ABSTRACT : While generative accounts of language processing assume that children break down language into smaller components on which they apply computational operations, usage-based accounts assume that children acquire frequently co-occurring words as large chunks, which they decompose only later in development. We investigated the evidence for the multi-word representation of idioms like to let the cat out of the bag in 9- to 10-year-olds using eye-tracking and Event-Related Potentials. Both measures indicated that children rapidly predict idiom-final words ( bag ). However, although they are generally capable of rapidly predicting semantic associates for highly predictive endings of novel sentences (as demonstrated in a control experiment), within idioms they activate semantic associates ( basket ) only in a late processing stage. We conclude that children rapidly activate multi-word units for idioms and decompose these units only after a short delay during online processing. This effect might relate to unitary acquisition of idioms as assumed by usage-based accounts.